As significações dos jovens sobre a escola e seu projeto de futuro - Paulo, Humberto (2021)
This study adopted as a general objective to understand the meanings of young people inserted in a state public school in the city of São Paulo about the school and its project for the future. The context that constituted this research was a state public school, located in the East Zone of São Paulo city, a region of high social vulnerability and the subjects involved were ten high school students between fifteen and seventeen years old of both sexes. The study is based on the framework of Socio-Historical Psychology by Lev Vigotski and contributors. The methodology is based on a qualitative approach and to reach the proposed objective, we used three reflective collective meetings (online) and a reflective interview (online) with each participant and composed of guiding questions. The analysis and interpretation of the information took place in accordance with the proposal of the Meaning Nucleus of Aguiar and Ozella (2006, 2013) and Aguiar, Soares and Machado (2015). The implementation of the new High School model presents the Life Project as a mandatory curricular component, which is the focus of our research, which intends to present a critical view both in the notion of life project and in the phenomenon of Adolescence, understanding them from their perspectives multidetermination. The analysis carried out reveal the naturalization of adolescence as an expression of social contradictions and the importance of understanding the adolescent process within specific and historical contexts of suffering, and also the presence of contradictions in the conceptions about the public school: the school you dream of and the school you have. It is expected that the study will contribute to the reflection on teacher training processes, at an initial or continuing level, regarding the life project of young people and the possibilities of carrying out this work in the daily life of the school, since these subjects are the agents that, in fact, put educational policies into action at school